A Rare Case of Haemoptysis Revealing Aortic Coarctation in an Adult - Ben Saad, Ahmed (Eur J Case Rep Intern Med, 2020)
Haemoptysis is a frequently occurring but sometimes life-threatening condition. Congenital cardiovascular abnormalities are rare causes of haemoptysis. We report a case of a 33-year-old man without any past medical history complaining of haemoptysis with no other associated clinical manifestations. A contrast-enhanced chest computed tomography scan revealed aortic coarctation with dilation of the internal mammary, intercostal and bronchial arteries. He underwent stent placement after balloon angioplasty with favourable outcomes. LEARNING POINTS: Adult patients with congenital cardiovascular abnormalities such as aortic coarctation may rarely, due to the high pressure and dilation in the bronchial arteries, present with recurrent haemoptysis as the sole clinical sign. A multidetector computed tomography scan contributes significantly to the aetiological diagnosis of haemoptysis in cases of congenital cardiovascular abnormalities. Interventional procedures such as stenting are currently the preferred approach for the treatment of aortic coarctation in adults, with good outcomes.